PENGGUNAAN DANA DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA TELUK NILAP KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR PROVINSI RIAU - Randi Darmawansyah; Syapsan Syapsan; Dahlan Tampubolon (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aims to analyze the relationship between the use of the Village Fund in the field of infrastructure development implementation on the welfare of the community and the use of the Village Fund in the field of community empowerment on the welfare of the people of Teluk Nilap Village, Kubu Babussalam District, Rokan Hilir Regency, Riau Province. The data used in this study is primary data using a cross sectional research design. This study uses the Spearman rank correlation analysis method with the help of SPSS for Windows version 24.0 software. From the results of the analysis, it can be said that the allocation of the Teluk Nilap Village Fund, Kubu Babussalam District, Rokan Hilir Regency in the field of infrastructure development has a positive and significant relationship with increasing community welfare. The allocation of Teluk Nilap Village Funds, Kubu Babussalam District, Rokan Hilir Regency in the field of community empowerment has a positive and significant relationship with improving community welfare